Retreatment efficacy and safety of tocilizumab in patients with rheumatoid arthritis in recurrence (RESTORE) study. Issue 1 (January 2014) - Nishimoto, Norihiro; Amano, Koichi; Hirabayashi, Yasuhiko; Horiuchi, Takahiko; Ishii, Tomonori; Iwahashi, Mitsuhiro; Iwamoto, Masahiro; Kohsaka, Hitoshi; Kondo, Masakazu; Matsubara, Tsukasa; Mimura, Toshihide; Miyahara, Hisaaki; et al.
Abstract: Objectives To evaluate the safety and efficacy of retreatment with tocilizumab (TCZ) in patients who had participated in the DREAM study ( Drug free remission/low disease activity after cessation of tocilizumab [Actemar] monotherapy study) and had experienced loss of efficacy. Methods Patients were retreated with TCZ or other disease modifying antirheumatic drugs (DMARDs). Disease activity was measured using the 28-joint disease activity score (DAS28) for 12 weeks. Results A total of 164 eligible patients, including 161 who experienced loss of efficacy within 52 weeks of the DREAM study, resumed treatment: 157 with TCZ and 7 with DMARDs and/or infliximab. Of TCZ-treated patients, 88.5 % (139 patients) achieved DAS28 <2.6 within 12 weeks, whereas among patients treated with DMARDs and/or infliximab only 14.3 % (1 patient) achieved DAS28 <2.6. Adverse events were observed in 70 TCZ-treated patients (44.0 %), but no serious infusion reactions were observed. Conclusions Retreatment with TCZ was well-tolerated and effective in patients who had responded to the preceding TCZ monotherapy but had experienced loss of efficacy after cessation of TCZ.